Validation of the Professional Practice Environment Scale in Australian General Practice - Halcomb, E.; Davidson, Patricia; Caldwell, B.; Salamonson, Y.; Rolley, John (Wiley-Blackwell, 2010)
Purpose: To validate the Professional Practice Environment Scale (PPE) in Australian general practice. Methods: The PPE was modified slightly for appropriateness for the practice setting and administered to a sample of 342 Australian general practice nurses via an online survey tool. The factor structure of the 38-item PPE was examined using principal components analysis with Varimax rotation. Findings: An eight-factor solution accounted for 71.6% of the variance. Lowfactor loading (<0.3) or cross-component loadings were detected in eightitems. A comparison of Cronbach's alpha values demonstrated little change in the deletion of eight items from four of the eight related components. Conclusions: Findings demonstrated that a 30-item version of the PPE was reliable and valid for use to assess the professional practice environment of nurses working in Australian general practice. Clinical Relevance: A tool to measure the professional practice environmentin general practice is important as it will assist in monitoring the impact of the work environment on the recruitment, retention, and satisfaction of nurses in this setting.